Robust photocatalytic and photoelectrochemical functions of PrFe 1-xMnxO3 perovskite nanostructures. Issue 19 (1st October 2022) - Ilanchezhiyan, P.; Mohan Kumar, G.; Siva, C.; Cho, H.D.; Lee, D.J.; Kang, T.W.; Kim, D.Y.
Abstract: Perovskite nanostructures of PrFe1-x Mnx O3 with and without Mn ions were hydrothermally processed and extensively studied as photocatalysts and photoelectrocatalysts. The significance of Mn ions on the intrinsic characteristics of perovskites were initially evaluated to be in orthorhombic pbnm structure. PrFe1-x Mnx O3 was also examined to be made up of fine particle like structures. The effective replacement of Mn ions was affirmed through several structural characterization routes. The bonding of Mn ions in the perovskite architecture and their capacity to replace the Fe sites was additionally studied using X-ray photoelectron spectroscopic (XPS) measurements. The absorbance spectra augmented the potential of PrFe1-x Mnx O3 to serve as an effective photocatalyst in treating organic pollutants. Mn ions were also found to improve the defect sites in the nanomaterials, which actually played a vital role in influencing the photocatalytic and photoelectrochemical activities. The photocatalytic efficacy of Mn based perovskites was noted to be much better than their pristine counterparts through the comparative photocatalytic studies. The density of photocurrent values studied via photoelectrochemical experiments also supported the active role of Mn ions in boosting the water splitting performance. The impedance data studied via electrochemical route suggested the aid of Mn ions in accelerating the migration of charges readily to result with the observed results.